Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC - Chic Giménez, Òscar (2021)
This collection is a catalogue of otolith stored in a database.The database is regularly updated and at present (06/17/2014) it contains a total of 4556 high resolution images corresponding to 1381 species and 216 families from the Mediterranean Sea, Antarctic Ocean (Weddell Sea, Ross Sea, Antarctic Peninsula), Atlantic Ocean (Argentina, Uruguay, South-western Islands, Gulf of Mexico, USA, Canada, Baltic Sea, North Sea, Ireland Sea, Cantabric Sea, Portugal, Madeira, Canary Islands, Morocco, Cabo Verde, Senegal, Gabon, Namibia), Indic Ocean (Madagascar, Tanzania, Red Sea, Iran) and Pacific (Australia, New Zealand, New Caledonia, Muroroa, Peru, Ecuador, Canada, Alaska).AFORO website offers an open online catalogue of otolith images and its associated shape analysis through pattern recognition techniques applying Fourier transform (FT), curvature space scale (CSS) and wavelet analysis (WT). This site also includes an Automatic Taxon Identification such allows to search and identify directly using query images of otholits. Recently, AFORO has incorporated 3D otoliths.